Evolving Dynamics of Language Policy and Chinese Language Education in the Philippines: Future Direction and Challenges - Xu, Lei; Ayuyao, Nunilon G.; Jiang, Xingshan (International Journal of Language Education, 2024)
This paper presents a comprehensive analysis of the evolution of language policy in the Philippines, with a particular emphasis on the status, challenges, and future prospects of Chinese language education within the national framework. The study is structured into five distinct sections. Firstly, the historical development of language policies in the Philippines is explored, tracing the transitions from colonial to contemporary eras and assessing their implications for language education. Secondly, an in-depth exploration of the present landscape of Chinese language education is provided, evaluating its integration into the Philippine education system and the effectiveness of existing programs. Thirdly, a critical examination of the current state of local Chinese language teacher training is conducted, analyzing the approaches used to foster a sustainable local teaching workforce. Fourthly, strategic pathways for the next decade are outlined, focusing on the localization of Chinese language education in alignment with the plans of the Philippine Department of Education and broader educational objectives. Finally, the concluding section synthesizes insights garnered from the preceding sections, reflecting on the significance of these developments for the future of Chinese language education in the Philippines. It underscores the pivotal role of Chinese language education in promoting cultural and educational exchanges and facilitating the modernization processes in both China and the Philippines. By addressing these dimensions, the paper offers a comprehensive overview of the intersection between language policy and Chinese language education in the Philippines, providing valuable insights for policymakers, educators, and researchers engaged in language education and policy planning in multilingual and multicultural contexts.